169 Standardized ileal digestible amino acids and net energy contents in full fat and defatted black soldier fly larvae meals (Hermatia illucens) fed to growing pigs. (30th November 2020) - Crosbie, Michelina M; Zhu, Cuilan; Shoveller, Anna Kate; Huber, Lee-Anne
Abstract: Two experiments were conducted to determine the standardized ileal digestibility (SID) of AA (Exp. 1) and available energy (Exp. 2) in two black soldier fly larvae meal (BSFLM) sources [full fat (FF) and defatted (DF)] for growing pigs. Two corn starch-based diets were formulated with FF and DF BSFLM as the sole sources of AA. A nitrogen-free diet was also used and the corn starch:sucrose:oil ratio was kept constant among diets to calculate digestible energy. In Exp. 1, 8 ileal-cannulated barrows (25.1±0.41 kg initial BW) were used in a replicated 2 x 2 Latin square design (n = 8). In each period, pigs were adjusted to diets for 5d followed by 2d of continuous ileal digesta collection for 8 h. The SID of AA were calculated using basal endogenous losses for pigs fed a nitrogen-free diet. In Exp. 2, 8 barrows (23.4±0.54 kg initial BW) were used in a partially replicated Latin square design (n=8). In each period, pigs were adjusted to diets for 7d, followed by 5d of total urine and fecal grab sample collection, and 24hr in indirect calorimetry chambers to determine heat production. The SID of Arg, Val, Ala, and Pro tended to be less, and the SID of Met tended to be greater for the FF versus the DF BSFLM (P=0.034, 0.090, 0.053, 0.065, 0.074, respectively). Digestible, metabolizable, and net energy (4101 vs 3257±224 kcal/kg) were greater for the FF versus the DF BSFLM (P< 0.05). The ATTD of phosphorus, neutral detergent fiber, and acid detergent fiber were greater for the FF versus the DF BSFLM (P< 0.05). In conclusion, the SID AA in FF and DF BSFLM were high and similar to those of soybean meal. The FF BSFLM is a better source of available energy for growing pigs compared to DF BSFLM.